2016
DOI: 10.1038/onc.2016.285
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of MLV integration in the hematopoietic tumor genome

Abstract: Extensive research has been performed regarding the integration sites of murine leukemia retrovirus (MLV) for the identification of proto-oncogenes. To date, the overlap of mutations within specific oligonucleotides across different tumor genomes has been regarded as a rare event; however, a recent study of MLV integration into the oncogene Zfp521 suggested the existence of a hotspot oligonucleotide for MLV integration. In the current review, we discuss the hotspots of MLV integration into several genes: c-Myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…MLV genomes were integrated into Stat5, c-Myc, ZFP521, and other oncogenes in the lymphoma cell genome. Upregulation in expression of Stat5 and ZFP521 are not sufficient, as pre-B cell lymphomagenesis and a strain-dependent background are required [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…MLV genomes were integrated into Stat5, c-Myc, ZFP521, and other oncogenes in the lymphoma cell genome. Upregulation in expression of Stat5 and ZFP521 are not sufficient, as pre-B cell lymphomagenesis and a strain-dependent background are required [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…Second, the inserted retroviral element has the promoter or enhancer activity of the host proto-oncogene. The genome of human papilloma virus (HPV), hepatitis B virus (HBV), human T-cell adult leukemia virus (HTLV) [5], avian sarcoma virus (ASV) [6], feline leukemia virus (FeLV) [7], murine leukemia virus (MLV) [8][9][10][11][12][13], and mouse mammary tumor virus (MMTV) can be integrated in the host genome. As a survival strategy, the inserted retroviral genome (provirus) is thereafter replicated during host cell division.…”
Section: Viral Genome Integrationmentioning
confidence: 99%
“…Through the recognition of open chromatin structure, BET proteins have been suggested to contribute to the tethering of the MLV PIC to the host chromatin [10,12]. Furthermore, it has been shown that the cell-permeable small molecule JQ-1, a pan-BET bromodomain inhibitor, prevents the BRD4-acetylated lysine interaction by competitively binding to BRD4 and reduces MLV integration frequencies at transcription start sites [4,13,14]. These findings suggest that BET proteins navigate the MLV genome and promote efficient MLV integration around transcription start sites associated with a chromatin structure characteristic of an open, transcriptionally active domain [3].…”
Section: Interaction Partners For MLV Integrase and Recent Developmenmentioning
confidence: 99%
“…In the experimental model, transgenic mice carrying chimera genes, such as Emu-myc mice, MT-BCR-ABL Lymphocyte Updates -Cancer, Autoimmunity and Infection mice, [6,7], and TEL/AML1 mice rapidly develop pre-B LBL [8][9][10]. Unlike these models, the SL/Kh mouse develops spontaneously in the absence of artificially introduced gene mutation; however, Zfp521 is the gene that is spontaneously and constitutively mutated by MLV insertion after the birth [11,12].…”
Section: The Characterization Of Spontaneous Pre-b-cell Lymphoma In Smentioning
confidence: 99%